2016
DOI: 10.1159/000438660
|View full text |Cite
|
Sign up to set email alerts
|

Pttg1 Promotes Growth of Breast Cancer through P27 Nuclear Exclusion

Abstract: Background/Aims: A role of Pituitary Tumor Transforming Gene 1 (Pttg1) in the carcinogenesis has been shown in some cancers, but not in BC (BC). Methods: We compared the levels of Pttg1 in the resected BC tissue with the adjacent normal breast tissue from the same patient. We modified Pttg1 levels in a BC cell line, MCF7, by either a Pttg1 transgene, or a Pttg1 shRNA. The cell growth was measured in an MTT assay. The cell apoptosis was measured by apoptosis assay. The nuclear protein of cell-cycle-related gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…PTTG1 is a regulator in chromosomal segregation. It can promote the proliferation of breast cancer cell through binding to P27 directly to induce nuclear exclusion of P27 16. MCM4 gene encodes a kind of minichromosomal maintenance proteins.…”
Section: Discussionmentioning
confidence: 99%
“…PTTG1 is a regulator in chromosomal segregation. It can promote the proliferation of breast cancer cell through binding to P27 directly to induce nuclear exclusion of P27 16. MCM4 gene encodes a kind of minichromosomal maintenance proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary tumor-transforming 3, pseudogene (PTTG3P), is a processed pseudogene that shows high homology to its family members, pituitary tumor-transforming 1 (PTTG1) and -2 (PTTG2) 8 . Numerous investigations have shown that PTTG1 and -2 serve as two key oncogenes in a variety of human cancers, including breast cancer,9, 10 lung cancer, 11 pituitary adenoma, 12 and esophageal squamous cell cancer 13 . However, there are only a few reports regarding the expression and roles of PTTG3P in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these hub genes were reported as critical players in regulating occurrence and development of breast cancer. For example, Zhang et al found that nuclear AURKA acquired kinase-independent transactivating function to enhance breast cancer stem cell phenotype (32); PTTG1 promoted growth, endocrine therapy resistance of breast cancer (33)(34)(35); UBE2C post-transcriptionally upregulated by miR-196a enhanced proliferation of breast cancer cell (36). Then, we performed survival analysis for the 51 hub genes.…”
Section: Discussionmentioning
confidence: 99%